Case Study: Student’s Response Towards Online Learning in Engineering Education During COVID-19 Pandemic - Kaur, Rashpinder; Garg, Arshia; Kaur, Prinkaldeep (Journal of Engineering Education Transformations, 2021)
Novel Corona virus Disease (COVID-19) originated from Wuhan, China is widespread across the world so World Health Organization has declared COVID-19 as pandemic. As there is no vaccine available and this disease is transmitted though air so social distancing is one of the widely adopted strategy to control the spread of the COVID-19 pandemic. The education process all over the country was suspended due to announcement of National Lockdown in April, 2020 by the government of India. The Teaching Organizations and Management of Engineering Colleges and Universities in India during this Lockdown Period took initiative to continue education and teaching with Information Technology. This study attempted to investigate the quality of engineering education through online platforms in terms of knowledge gain, concept clarity, assessment, satisfaction level of students during the COVID-19 pandemic. An online survey was conducted and 123 student’s responses were received. The student’s response towards the online learning leads to conclusion that although the use of technologies in education is increased a lot but still learning through online mode will remain as supplementary material for the students. It cannot replace the traditional classroom teaching.